Susceptibility of two populations of Aedes aegypti (Diptera: Culicidae) of Cali (Valle, Colombia) to Temefos (Abate®) and Triflumuron (Starycide®) - PRIETO, AYDA VIVIANA; SUÁREZ, MARCO FIDEL; GONZÁLEZ, RANULFO (Revista Colombiana de Entomología, 2002)
In the context of the integrated vector management, chemical control continues to be an important strategy if it is used in rational and controlled ways. The objective of the present work was to determine the susceptibility of Aedes aegypti larvae to formulations used in the public health of Temephos and Triflumuron in three areas of Cali city. The populations analyzed were highly susceptible to both insecticides. Mortality ratios for Temephos ranged between 98.7 and 96.0%, displaying an apparent reversion of the resistance showed in 1996. Based on the results it is possible to suggest the alternate use of both products in the frame of an integrated management program but with a previous evaluation of the Triflumuron cost-benefit grounds.